Petani Madu Sialang Dalam Kekuatan Solidaritas Mekanik dan Organik (Studi Tentang Petani Madu Sialang Di Desa Kuala Panduk, Kec. Teluk Meranti, Kab. Pelalawan) - Melisa, Melisa; Tantoro, Swis; Asriwandari, Hesti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to find out how mechanical and organic solidarity mobilize Sialang honey production activities and also understand the strengths and weaknesses of mechanical and organic solidarity in the production activities of Sialang honey. This study uses a qualitative approach with descriptive methods.The results showed mechanical solidarity in the production activities of Sialang honey, as seen in the honey harvest process, where all honey farmers still have very close family ties and the trust of the farmers in customary norms is still very strong. If there is a conflict, then the principal will not produce honey again. Farmers avoid all types of conflicts, and if there is a conflict over honey, farmers will also take family paths in resolving the conflict so that basic sustainability is maintained. However, mechanical solidarity alone is not enough to market honey, so assistance is needed from other parties, namely the intervention of CSR PT RAPP in providing training and assistance in the processing, sales, and marketing of honey so that organic solidarity is formed. The strength of organic solidarity in Sialang honey production activities includes: Penetration of the Sialang Honey Sales Market, Starting from Pangkalan Kerinci, Pekanbaru, to Jakarta Sialang honey, which was previously not sold by honey farmers, has now been sold both offline and online. The use of technology to reduce water content so that honey becomes thicker attracts people to buy honey, and people believe in the quality of honey. The existence of the brand itself under the name of honey foresbi," which distinguishes Sialang honey from other honey.